2021
DOI: 10.1007/s42452-021-04803-1
|View full text |Cite
|
Sign up to set email alerts
|

N and Fe doped NiO nanoparticles for enhanced photocatalytic degradation of azo dye methylene blue in the presence of visible light

Abstract: Pure NiO, N-doped, Fe-doped, N and Fe codoped NiO NPs were fabricated via a precipitation process. The powder X-ray diffraction (XRD) revealed the face centered cubic phase of NiO products. The full width at half maximum (FWHM) of the XRD peak was steadily enlarged with the order of elements N, Fe, N/Fe doped to NiO, and shifted towards a greater angle due to decrease in grain size, as shown by XRD. The average crystallite size of NiO products was calculated, ranging from 6.67 to 3.76 nm, according to the Deby… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(2 citation statements)
references
References 44 publications
2
0
0
Order By: Relevance
“…The KNO (Figure 2b) 2θ angles of 37.24 , 43.28 , 62.88 , 75.42 , and 79.40 for (hkl) planes (111), (200), (220), (311), and (222), respectively. 36,[55][56][57] PANI (Figure 2a) broad peaks (characteristics peaks) were observed at 15.05 , 20.59 , and 25.25 (2θ angles) in accordance with already reported results. 37,38,40,58,59 The XRD micrograph of composites revealed the increased intensities of KNO peaks with an increased amount of KNO in PANI.…”
Section: X-ray Diffractionsupporting
confidence: 92%
“…The KNO (Figure 2b) 2θ angles of 37.24 , 43.28 , 62.88 , 75.42 , and 79.40 for (hkl) planes (111), (200), (220), (311), and (222), respectively. 36,[55][56][57] PANI (Figure 2a) broad peaks (characteristics peaks) were observed at 15.05 , 20.59 , and 25.25 (2θ angles) in accordance with already reported results. 37,38,40,58,59 The XRD micrograph of composites revealed the increased intensities of KNO peaks with an increased amount of KNO in PANI.…”
Section: X-ray Diffractionsupporting
confidence: 92%
“…We can split the transmittance spectra into two ranges: the first one at a wavelength lower than 400 nm for which transmittance is almost inexistent and where it exhibits the beginning of absorption owing to the direct transition between the valence and conduction bands. The second is at a wavelength greater than 400 nm showing the transparency of NiO films whose transmittance yield depends on Cu-doping concentration, in agreement with the literature where Mn, Zn, and Fe doping were used [44,45]. It is observed that with increasing Cu-doping, there is a decrease in transmittance and an increase in the absorbance attributed to changes in the crystalline structure due probably to the increase in NiO film thickness as indicated in XRD results.…”
Section: Optical Propertiessupporting
confidence: 88%